Mission critical Windows 2000 server administration ([U.S.] : Syngress Media ; London : International Thomson, 2000)
Announcing the "Mission Critical" series from Syngress Media - providing crucial coverage of the topics necessary for IT professionals to perform and succeed on the job. Mission Critical Windows 2000 Server Administration cuts to the chase and provides system administrators with the most important features of the operating system. There's no "hand-holding", no basic definitions of functions, no step-by-step guidelines - just high-level coverage of the critical components of Windows 2000 that system administrators must know. * Hot topic - since the launch of Windows 2000 in February - there is an increased demand for a high-level book * Comes with free membership to Solutions@Syngress.com, which provides readers with regular updates, articles, white papers, and bug alerts * Offers high-level coverage of the following topics: Active Directory, remote installation and deployment, security, network services, Microsoft Management Console and administration.
Keywords: Microsoft Windows (Computer file).; Electronic books